Approach to An Unusual Cardiac Mass: Mitral Annulus Caseoma - Pala,Arda Aybars (2020)
Abstract Caseous calcification of the mitral annulus (CCMA) is known to be a rare variant of mitral annulus calcification, a chronic and degenerative process of the mitral valve fibrous ring. It usually carries a benign prognosis. The following case demonstrates a huge mitral annulus caseoma that complicated with severe mitral regurgitation and was treated with a successful surgery. The common consensus on the optimal management of CCMA is conservative medical management and avoiding unnecessary surgery. Therewithal, the current indications for surgical intervention include mitral valve dysfunction, strokes and uncertain diagnosis. Aggressive debridement, risk of left ventricular perforation and exposure of caseous debris to the systemic blood flow may increase the risk of a standard mitral valve surgery. Mitral valve replacement should be preferred compared with mitral valve repair.